2003
DOI: 10.1046/j.1472-765x.2003.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes occurrence and characterization in meat-producing plants

Abstract: Aims:The prevalence, level of contamination and epidemiological profile of Listeria monocytogenes were investigated in two meat-producing plants during a 20-month period. Methods and Results: Sampling for L. monocytogenes was carried out in a cattle slaughterhouse (n ¼ 72) and a swine meat-processing plant (n ¼ 68) during a 20-month period. Swabs and food samples were analysed with the most probable number (MPN) technique for L. monocytogenes and the isolated strains were characterized by AscI-restriction anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 17 publications
2
37
0
7
Order By: Relevance
“…Prevalence data from this research are consistent with several authors who have pointed out that processing plants are not a significant source of L. monocytogenes contamination. (23)(24)(25)(26)(27). …”
Section: Discussionmentioning
confidence: 99%
“…Prevalence data from this research are consistent with several authors who have pointed out that processing plants are not a significant source of L. monocytogenes contamination. (23)(24)(25)(26)(27). …”
Section: Discussionmentioning
confidence: 99%
“…Meat products are a major source of L. monocytogenes (9,21,22,24,27,29,32). As clinical cases of listeriosis are usually associated with high loads of L. monocytogenes (10, 11) and as it is difficult to eradicate listeriae from the environment of the food processing plants (12), the International Commission on Microbiological Specification for Foods concluded that 100 CFU of L. monocytogenes per g of food at the time of consumption is acceptable for nonrisk consumers (14,19).…”
mentioning
confidence: 99%
“…L. monocytogenes can easily contaminate raw meat during animal slaughtering and meat processing, and it can persist on contaminated surfaces of processing plants for long periods of time. It can also survive or grow in products across wide ranges of pH and a w , even in the presence of nitrite and nitrate, and at refrigeration temperatures [2,13,15]. Before December 2005, according to the Italian food regulations, there was no tolerance allowed for the presence of L. monocytogenes in readyto-eat meat products in Italy, whereas in other European countries, different criteria for tolerable levels of this pathogen had been established on the basis of risk assessment studies [14].…”
Section: )mentioning
confidence: 99%